C reactive protein and immunoglobulin G in synovial fluid and serum in joint disease. Issue 1 (January 1991) - Shine, B; Bourne, J T; Begum Baig, F; Dacre, J; Doyle, D V
Abstract : C reactive protein (CRP) and immunoglobulin G (IgG) were measured in synovial fluid and serum of 72 patients (29 with rheumatoid arthritis (RA), 17 with osteoarthritis, 11 with crystal synovitis, seven with undifferentiated arthritis, and eight with seronegative arthritis). The synovial fluid:serum (SF:S) ratios were compared with those calculated from the SF:S ratios of transferrin, caeruloplasmin, and alpha 2 macroglobulin, using the binomial test within groups and the Mann-Whitney test between groups. In RA synovial fluid CRP concentrations were lower than expected and IgG concentrations higher than expected. In osteoarthritis CRP concentrations were higher than expected. In seronegative arthritis IgG concentrations were raised. The ratio of CRP:IgG was depressed in RA. These findings are consistent with a role for CRP in the inflammatory process of RA, while the CRP:IgG ratio may be of value in the differential diagnosis of joint disease.